Gut microbiota modulate immune responses to orally and parenterally administered rotavirus in mice - Zhenda Shi; Sung-Sil Moon; Jun Zou; Yanling Wang; Noopur Bhatnagar; Vu L. Ngo; Xiaoqian Wang; Houping Wang; Theresa K. Bessey; Jennifer J. Hull; Yuhuan Wang; Sang-Moo Kang; et al. (npj Vaccines)
Abstract Rotavirus (RV) remains a significant cause of infantile morbidity and mortality, while oral RV vaccines offer inconsistent protection. This study investigates whether gut microbiota influence immune responses to orally and intramuscularly (IM) administered RV strains. Using murine models, we identified microbiota constituents, including segmented filamentous bacteria, reducing oral RV infection and RV antibody generation. Such blockade of RV-induced responses was associated with elevated expression of intestinal Reg3β and Reg3γ and was recapitulated by intraperitoneal administration of cognate recombinant proteins. IM administration following oral RV inoculations enhanced antibody production and defense against RV challenge. We further showed microbiota composition also influenced the efficacy of a single IM RV inoculation. Antibiotic-induced microbiota depletion boosted IM RV efficacy in poorly responding animals. Such enhancement of IM RV-induced immunity appeared to be associated with increased expression of serum RANTES and Eotaxin. The phenotype was recapitulated by directly adjuvating these chemokines to the IM inoculum.